Retinal Identification Based on Rotation Invariant Moments - Dehghani, Amin; Moghaddam, Hamid Abrishami; Moin, Mohammad-Shahram (2011 5th International Conference on Bioinformatics and Biomedical Engineering, 2011)
In this paper, we propose a new identification method based on the retinal images. In this algorithm, we use rotation invariant features extracted from the retinal images. Then, we use them for identification. Experimental results on a database, including 60 retina images obtained from 40 subjects of DRIVE database and 20 subjects from STARE database, show the average true identification accuracy rate equal to 99.78 percent for the proposed algorithm.